2002
DOI: 10.1007/s00213-002-1046-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forced swimming-induced stress on the anxiolytic-like effect of 5HT1A agents in mice

Abstract: The present data provide evidence that FS induces changes in the effect of 5-HT(1A) agents. The participation of the 5-HT and/or GABA systems in these stress-induced effects is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 71 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…The low dose of E-6837 reversed the increase in climbing behavior found with ketamine, a result not observed with the high dose. These findings coincide with a previous report of bidirectional effects on the level of anxiety recorded in mice that had been stressed and treated with distinct doses of buspirone, a partial 5-HT1A agonist (Briones-Aranda et al, 2002). This evidence indicates the importance of external factors in the regulation of specific behaviors as ketamine treatment (Ikeda et al, 2011) and stress (Briones et al, 2015) increase the concentration of brain DA and 5-HT, which in turn could influence the actions of nonselective serotonergic agents.…”
Section: Discussionsupporting
confidence: 89%
“…The low dose of E-6837 reversed the increase in climbing behavior found with ketamine, a result not observed with the high dose. These findings coincide with a previous report of bidirectional effects on the level of anxiety recorded in mice that had been stressed and treated with distinct doses of buspirone, a partial 5-HT1A agonist (Briones-Aranda et al, 2002). This evidence indicates the importance of external factors in the regulation of specific behaviors as ketamine treatment (Ikeda et al, 2011) and stress (Briones et al, 2015) increase the concentration of brain DA and 5-HT, which in turn could influence the actions of nonselective serotonergic agents.…”
Section: Discussionsupporting
confidence: 89%
“…BDNF regulates synaptic transmission and activitydependent plasticity (Bramham & Messaoudi, 2005 ;Gottmann et al 2009), promotes neurogenesis (Scharfman et al 2005) and exerts an antidepressant activity in a time-dependent manner, as it has been shown that a single bilateral infusion of BDNF into the dentate gyrus of the hippocampus produces an antidepressant-like effect in both the learned helplessness paradigm and FST, within 3 d after infusion (Shirayama et al 2002). Importantly, pre-training stressors that affect behavioural response induce neuronal plasticity changes (Briones-Aranda et al 2002 ;Chaki et al 2004 ;Consoli et al 2005 ;Drago et al 2001 ;Micale et al 2008b ;Pittenger & Duman, 2008 ;Tamburella et al 2010 ;Teixeira & de Lima, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Because stressful life events are major predisposing risk factors for developing depression, preclinical studies should take into account both the effects of pre-training stressors, such as drug injection procedure, inescapable foot-shocks, restraint and forced swim on the behavioural and neuroendocrine responses of animals, and the influence of these stressful stimuli on anxiolytic and/or antidepressant drug action (Briones-Aranda et al 2002 ;Consoli et al 2005 ;de Kloet et al 2005 ;Drago et al 2001 ;McEwen, 2005 ;Micale et al 2008a ;Tamburella et al 2010 ;Teixeira & de Lima, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Present animal models and tests most likely provide partial data about the behavior under study. For example, different tests of anxiety-like behaviors in rodents and different methodological approaches show distinct predictive validity and non-similar effects of anxiogenic or anxiolytic pharmacological compounds [130][131][132]. Moreover, our first experimental approach has been applied to test the behavior of adult males to avoid confounding variations due to cyclical changes in circulating sex hormones [40,65,133].…”
Section: Functional Features Of the Medial Amy-gdalamentioning
confidence: 99%